Standar Isi, Bahasa, dan Penyajian Buku Tematik Terbitan Mediatama Tema 7 Indahnya Keragaman Seri HOTS - Mia Nurkhofifah; Sudirman Sudirman; Muhammad Tahir (Journal of Classroom Action Research, 2022)
Textbooks that have been used in schools contain chapter openings, contextual problems, summaries, exercises, student activities, student assignments and the use of technology (computers). However, in the book the presentation of the material has not been able to make students active. This study aims to determine the conformity of content standards, language standards, and presentation standards of thematic books published by Mediatama, theme 7 The Beauty of Diversity in my Country, the HOTS series for class IV curriculum 2013 with the standards set by the National Education Standards Agency (BSNP). The approach used in this research is a qualitative approach and the type of research is content analysis. The data collection method used is the study of documentation. The research instrument is the researcher himself who is assisted by a research instrument in the form of a book assessment standard that has been set by BSNP. The data analyzed in this study is the standard of content/material, language, and presentation in the textbooks of Class IV SD/MI students Theme 7 The Beauty of Diversity in My Country, the 2013 Curriculum HOTS Series published by Mediatama. The results of the analysis show that the percentage of conformity of content standards is 91.65% (very appropriate), language standards of 94.44% (very suitable), and presentation standards of 91.66% (very suitable).